Editorial Message - Preudhikulpradab, Sirichai (ABAC ODI JOURNAL Vision. Action. Outcome, 2024)
As we present this latest edition of our journal, we are excited to showcase a diverse array of studies that contribute to the fields of hospitality and tourism management, organizational development, education, and human resource development. Each article highlights unique challenges and opportunities for change and improvement, reflecting the dynamic landscape of contemporary research. Hospitality and Tourism Management looks into employee retention at a Thai hotel, showcasing how a supportive work environment can enhance staff loyalty and guest satisfaction. We also explore the journey of hospitality professionals transitioning into teaching, illustrating the valuable exchange of industry expertise and academic insights. Organizational Development highlights the significant impact of strategic interventions in fostering innovation and improving job performance. These studies remind us that investing in people is essential for achieving organizational success. Education and Leadership emphasize the power of leadership and collaboration. Articles on enhancing teacher leadership and nurturing student creativity reveal how cultivating these qualities can create vibrant learning communities that inspire future generations. Lastly, Human Resource Development focuses on employee happiness and the critical role of HRD professionals in shaping effective organizational structures. By prioritizing well-being, we pave the way for a more engaged and motivated workforce, including the importance of social responsibility, urging a commitment to ethical practices, and active community engagement. As you explore these studies, we hope you feel inspired to take action and drive meaningful change within your organizations and communities. Thank you for your continued support, and we look forward to your feedback in future editions! Warm regards, Sirichai Preudhikulpradab, Ph.D. Ed. D Editor ABAC ODI Journal Vision. Action. Outcome October 2024